Effect of Sheath Current on the Lead Sheath of 115kV XLPE Underground Cable - Jariyanurat, Kittipod; Jeenmuang, Siwakorn; Chumpiboon, Komin; Kerdmanee, Sittipong; Lacharochana, Sakda; Pattanadech, Norasage (My University, 2024)
Currently, underground cable systems are extensively employed in power generation and distribution due to their superior reliability, stability, and safety. Given the significant investment and critical role of these systems, it is essential to rigorously assess their lifetime and performance. Key factors affecting the lifespan and life assessment of underground cables include the insulation system and the physical components of the power cable. Among these, sheath current is a notable factor that contributes to cable deterioration. This paper investigates the impact of prolonged sheath current on XLPE power cables, which have been in operation for approximately 25 years, associated with a 115kV generator unit. Specifically, the study focuses on the degradation of the lead sheath due to sheath current exposure. It was observed that the lead sheath exhibited signs of degradation, including tracking, which affected various layers, such as the lead sheath itself, the semi-conductive tape, and the semi-insulation. The research highlights that while sheath current did lead to observable tracking on the lead sheath, the overall impact on the cable's lifetime was minimal. An analysis of the lead sheath's properties, based on fundamental physical characteristics, revealed that long-term exposure to sheath current primarily caused minor physical tracking on the sheath's surface rather than significantly affecting its lifespan. This finding suggests that although sheath current can induce localized degradation, its effect on the overall functional longevity of the lead sheath is relatively limited.
Keywords: lead sheath; sheath current; underground cable; XLPE